Interações inesperadas da estruturação do substrato por plantas emergentes afetando o estabelecimento de macrófitas submersas enraizadas. - Dainez Filho, Mário Sérgio (2017)
The flooding of emergent plants after an extreme drought confers a new sediment structuration. This study tested the hypotheses that (i) the submersed macrophytes occurrences decrease in sites where the sediment is structured by emergent macrophyte flooded biomass, and that (ii) the sediment structured by the biomass one emergent maccophyte (Urochloa arrecta) recently flooded hinder Egeria najas? and Hydrilla verticillata colonization; (iii) the submersed invader (H. verticillata) is less affected than E. najas owning to its better colonization potential, and (iv) the structured sediment by U. arrecta would promote higher dissolved nutrient release than the non-structured sediment. It was collected data about the occurrence of submersed macrophytes in sites with and without structuration by biomass of emergent macrophytes that were flooded two years before this study. It was also experimentally assessed the submersed macrophytes relative growth rates and the root investment on four kinds of substratum structuration provided by U. arrecta; by P. ferrugineum; artificially structured and by non-structured sediment. Divergence between the experimental and the observational approaches revealed that the interactions between emergent and submersed macrophytes, as the species studied in this work, should not be neglected. Owning to the high dominance of these species (highlighting the invasive U. arrecta), the nutrient inputs promoted by their decomposition could increase the invisibility, facilitating the establishment of invasive submersed macrophytes, as verified in our experiments. At the same time, if invaders propagules pressure is low at the nutrient release stage, death biomass accumulation seems to inhibit their growth, as verified in situ.